Translation, validity and reliability of Evaluation Process within Supervisory Inventory (EPSI) among trainee counselors in public universities in Malaysia - Arifin, Suhaili; Mohd Noah, Sidek; Wan Jaafar, Wan Marzuki; Zakaria, Noor Syamilah (Human Resource Management Academic Research Society, 2019)
This study is carried out to translate the Evaluation Process Within Supervisory Inventory (EPSI) from English version to Malay language, then to test validity and reliability of the instrument. This EPSI is developed by Lehrman-Waterman & Ladany (2001) to measure the perception and experience of the trainee counselor towards the evaluation process in the clinical supervision. The translation procedure in this study uses the back-to-back translation method with the appointment of six experts from the counseling field. All these experts are proficient and fluent in both languages based on the local values and culture. The first phase involves three experts translating the EPSI into Malay language, whereas the rest of the experts retranslated the instrument back to English. For content validity, the EPSI already translated in Malay language is sent to the three other experts in the field for the evaluation of the item content and the sub-scale used in the instrument. The result indicates the coefficient value of content validity obtained for each item is high with maximum value =.933 and minimum value =.767, while the coefficient value for each sub scale also high with goal setting =.890 and feedback =.883. Finally, the reliability value of EPSI in the pilot study for goal setting ?=.958 and feedback ?=955; whereas in the actual study, for goal setting ?=.846 and feedback ?=.840 respectively. These values indicate that EPSI is a consistent instrument. In conclusion, other than successfully translating the Evaluation Process within Supervisory Inventory into the local context, this study also proves that the instrument also has good validity and reliability. Hence, it can benefit and applicable for Malaysian trainee counselors.